Sprachkontakt generativ Eine Untersuchung kontaktbedingten syntaktischen Wandels im Zimbrischen - Bidese, Ermenegildo (Linguistische Arbeiten, 2023)
This book makes a theoretical contribution to research on the dynamics and processes of structural language contact and language change resulting from contact. It also provides insights into the syntax of Cimbrian, one of the oldest German-based dialects outside the German Sprachraum, and aims to provide a model for establishing a field of Germanist language contact research.